Structural diversity and catalytic properties of five Co2(COO)4 cluster-based coordination polymers modified with R-isophthalic acid (R = H, NO2, CH3, OH and tBu). Issue 34 (7th August 2017) - Zhang, Jian-Yong; Shi, Jun-Xia; Cui, Peng-Hui; Yao, Zi-Jian; Deng, Wei
Abstract : By regulation the substituents on 5-position of isophthalic acid, we isolated five Co-based CPs with structural diversity, which all constructed from the Co2 (COO)4 unit. The catalytic properties for Knoevenagel condensation and selective epoxidation of styrene have also been investigated. Abstract : The self-assembly of 5-substituted isophthalic acid (R-H2 BDC, R = H, –NO2, –CH3, –OH and – t Bu), Co II ions and 2, 4, 6-tris(4-pyridyl)-1, 3, 5-triazine (TPT) under solvothermal conditions yielded five Co-based coordination polymers (CP s): [Co(BDC)(TPT)]·0.5(H2 O) n (CP 1 ), [Co(NO2 -BDC)(TPT)]·H2 O n (CP 2 ), [Co(CH3 -BDC)(TPT)]·0.5H2 O n (CP 3 ), [Co(HO-BDC)(TPT)]·0.5H2 O n (CP 4 ), and [Co( t Bu-BDC)(TPT)2/3 ]·(CH3 CH2 OH)(H2 O) n (CP 5 ) (H2 BDC = isophthalic acid, NO2 -BDC = 5-nitroisophthalic acid, CH3 -BDC = 5-methylisophthalic acid, OH-BDC = 5-hydroxyisophthalic acid and t Bu-BDC = 5- tert -butylisophthalic acid). All compounds comprise Co2 (COO)4 binuclear units, which are connected via a combination of R-H2 BDC and TPT ligands. InCP 1, the binuclear Co2 (COO)4 units are bridged into 1D chains extending along the [1 1 0] and [−1 1 0] directions, which are further interlinked by TPT ligands into a 3D network with CdS net topology.CP 2, CP 3 andCP 4 are iso-structural and all exhibit 3D frameworks with pcu (α-Po) topology. InCP 5, the Co2 (COO)4 units are firstly linked into a 3D NbO net via t Bu-BDC ligands, which are further accommodated by size-matching trigonal TPT ligands into a novel (3, 8)-connected 3D net. Catalytic measurements show thatCP 2 andCP 3 are good catalysts for the Knoevenagel condensation reaction of benzaldehyde with ethyl cyanoacetate, exhibiting conversions of 91.3% and 96.6% in 120 min, respectively, compared with the other present compounds. In addition, CP 2 andCP 5 exhibit highly efficient catalytic properties for the selective epoxidation of styrene.